Phenotypic findings due to trisomy 7p15.3-pter including the TWIST locus - Stankiewicz, Paweł; Thiele, Hannelore; Baldermann, Christiane; Krüger, Antje; Giannakudis, Ioannis; Dörr, Sylvia; Werner, Nadeshda; Kunz, Jürgen; Rappold, Gudrun; Hansmann, Ingo (American journal of medical genetics, 2001)
We report on a three-month-old boy with a 46,XY,der(Y)t(Y;7)(p11.32;p15.3) karyotype and growth deficiency, postnatal microcephaly with large fontanels, wide sagittal and metopic sutures, hypertelorism, choanal stenosis, micrognathia, bilateral cryptorchidism, hypospadias, abnormal fingers and toes, and severe developmental delay. FISH studies showed partial trisomy 7p resulting from a de novo unbalanced translocation. The application of molecular probes from the TWIST gene region (7p15.3-p21.1) and probes from the pseudoautosomal region (PAR) demonstrated that the 7p15.3-pter fragment was translocated onto Yp with the breakpoint within ∼20 kb from the Yp telomere. We discuss the possible role of the TWIST gene in abnormal skull development and suggest that trisomy 7p cases with delayed closure of fontanels can be a result of TWIST gene dosage effect. © 2001 Wiley-Liss, Inc.